Morphological Characteristics and Economic Value of Mangroves (Rhizophora and Avicennia) in Penunggul Village, Pasuruan Regency, East Java, Indonesia - Imamah, Sri Wahyu; Pujiastuti, Pujiastuti; Asyiah, Iis Nur (BIOEDUKASI, 2024)
Mangroves are ecosystems with high productivity levels and functions from an ecological/biological, physical, and economic perspective. Mangroves have a high diversity of plant species. The morphological and anatomical adaptations of mangrove species are very relevant from an ecological point of view. Generally, the dominant plants in mangrove ecosystems usually come from Rhizophora, Avicennia, and Sonneratia genera. Indonesia is a country with the highest mangrove forest area in the world. Mangrove ecosystems spread across almost all islands, one in East Java, precisely in Penunggul Village, Pasuruan Regency. Can study the potential of the mangrove ecosystem in Penunggul village from an ecological and economic perspective. To explore information related to mangrove plant diversity in Penunggul Village with morphological observations of plants and compare with the literature. Can explore the economic value of mangroves in Penunggul Village by conducting interviews with people who utilize mangroves in terms of monetary value. The dominant mangrove plants found in Penunggul Village are R. mucronata, R. stylosa, A. alba, and A. marina. The community uses the economic potential of mangroves in seedlings, chip production, and buying and selling marine biota that live around mangrove ecosystems, such as oysters and crabs.